An Empirical Study on the Relationship between Craftsman’s Spirit and Economic Growth of Construction Industry - Furong Bai; Huanru Wang (Advances in Multimedia)
This exploration aims to explore the relationship between craftsman’s spirit and the economic growth of the construction industry and discuss the heterogeneity of different regions to provide a reference for the development of the construction industry in each region. The annual data from 2011 to 2018 of China’s 30 provinces (autonomous regions and municipalities) (except Tibet) is used as the research object. Based on defining the craftsman’s spirit of the construction industry and constructing its comprehensive evaluation index system, a panel data model is established to analyze the relationship between the craftsman’s spirit and the economic growth of the construction industry and regional differences. The empirical results show that the level of craftsman’s spirit in China’s construction industry is increasing year by year, showing a “gradient decreasing” trend in the east, the middle, and the west. Specific data show that, from 2011 to 2018, the craftsman’s spirit of the construction industry in 30 provinces increased from 0.154 to 0.256. Among them, the craftsman’s spirit index in Beijing in 2018 was 2.19 times higher than that in 2011, an increase of 119.38%, with the fastest growth rate. The growth rate of Shaanxi Province in recent 8 years is only 11.4%, which is relatively low. The craftsman’s spirit has a positive impact on the economic growth of the construction industry, and there are regional differences. The promotion effect is more obvious in the central region, followed by the eastern region, and weaker in the western region. The research content has important reference value for improving the construction industry’ attention to cultivating the craftsman’s spirit of employees and promoting the coordinated development of regions.